2002
DOI: 10.1128/aac.46.11.3463-3471.2002
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Therapy forBacillus anthracis-Induced Polymicrobial Infection in60Co γ-Irradiated Mice

Abstract: Challenge with both nonlethal ionizing radiation and toxigenic Bacillus anthracis spores increases the rate of mortality from a mixed bacterial infection. If biological weapons, such as B. anthracis spores, and nuclear weapons were used together, casualties could be more severe than they would be from the use of either weapon alone. We previously discovered that a polymicrobial infection developed in B6D2F 1 /J mice after nonlethal (7-Gy) 60 Co ␥ irradiation and intratracheal challenge with B. anthracis Stern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In summary, we found that subcutaneous infection was a consistent and simple way to establish systemic anthrax in a mouse model. Because, unlike in humans, the skin in mice does not appear to be a significant barrier to systemic disease, we did not need more complex or invasive infection procedures used in other models such as aerosolization chambers or intratracheal injection (Albrink 1961;Dalldorf et al 1971;Fritz et al 1995;Elliott et al 2002;Vasconcelos et al 2003). Similarly, we did not need to use previously described intraperitoneal infection routes (Karginov et al 2004;Popov et al 2004), thereby avoiding direct and potentially confounding interactions of bacteria with intraperitoneally dosed anaesthetics and therapeutic compounds under study in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we found that subcutaneous infection was a consistent and simple way to establish systemic anthrax in a mouse model. Because, unlike in humans, the skin in mice does not appear to be a significant barrier to systemic disease, we did not need more complex or invasive infection procedures used in other models such as aerosolization chambers or intratracheal injection (Albrink 1961;Dalldorf et al 1971;Fritz et al 1995;Elliott et al 2002;Vasconcelos et al 2003). Similarly, we did not need to use previously described intraperitoneal infection routes (Karginov et al 2004;Popov et al 2004), thereby avoiding direct and potentially confounding interactions of bacteria with intraperitoneally dosed anaesthetics and therapeutic compounds under study in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Could long distance secretion facilitate cheating within anthrax infections? The existence of any mixed infections of B. anthracis and other toxin null Bc group bacteria remain unclear although polymicrobial infections involving B. anthracis are not unknown [84]. Loss of toxin-bearing plasmids also occurs quite readily in culture [85].…”
Section: Cereulide and B Anthracis Toxinsmentioning
confidence: 99%
“…Many of these models have used subcutaneous challenges and have been used primarily for vaccine development studies (7,25). Two recent reports did involve respiratory route challenges followed by antibiotic treatment, using a guinea pig intranasal challenge model (2) and an irradiated mouse intratracheal challenge model (16). The guinea pig model is limited due to the safety spectrum of antibiotics that can be tested in this model (32).…”
mentioning
confidence: 99%